Extraction and application of eco-friendly ratio natural Dye from Jamun on different fibers by using ratio Combination of Mordents - Liaquat, Lubna; Shahzadi, Dr.Phool; -un- Nisa, Alim; Ali, Zeeshan; Kalsoom, Razia; Rehman, Abdur (Indonesian Scientific Publication, 2024)
This paper reports to studies available on the characterization of the colorant extracted from the Jamun Bark dyeing on different fibers have been studies using different combination ratio 1:1, 2:1 of various mordant such as FeSO4oxalic acid, Sncl2, alum. It is found that Jamun Bark dye can be successfully used for the dyeing of Jute to obtain wide range of colors by using various combination of mordents. Development of new shade and analysis of colour parameter for textile dyes with Jamun Bark natural dyes with regard to colour fasteners properties. The test samples exhibit good to excellent